The effect of leadership styles on employee’s performance in Ethiopian sports organizations with mediating and moderating roles - Yifan Liu; Abyot Abdela Ali; Jiawen Pan; Yi Xiao (Scientific Reports)
Abstract The research explored the impacts of diverse leadership styles on employee performance in Ethiopian sports organizations. It specifically examined the mediating effects of job satisfaction and the moderating impact of education level. In this study a cross-sectional survey design was employed, with 463 participants from various sports organizations. Validated scales were used for the data collection of leadership styles, job satisfaction, and employee performance. The analysis of the data was conducted using descriptive statistics and structural equation modeling with software SPSS and Smart PLS4. The findings indicated that the perceived transformational leadership approach showed the strongest positive correlation with job satisfaction and employee performance, followed by the transactional leadership approach. In contrast, the laissez-faire leadership interaction with both employee job satisfaction and performance was demonstrated negatively. Job satisfaction was partially mediated in the relation between all three leadership styles and employee performance. Moreover, education level moderated the interaction between transformational leadership and job satisfaction. Drawing upon these findings, recommendations were provided for Ethiopian sports organizations to improve leadership styles and enhance employee performance, with a focus on understanding the mediating effect of job satisfaction and moderating effect of education level.